Effectiveness of teachers corrective feedback in improving students learning during task-based on speaking activities - Rugama Rodríguez , Beberly Tatiana | Inestroza Pérez, Ervin Francisco | Gómez Talavera, Marjorie Ninoska Gómez Talavera Marjorie Ninoska (Nicaragua | ESTELI UNAN-Managua, FAREM-Estelí, Nicaragua, 2022)
Oral corrective feedback and task-based learning have been two important pedagogical topics in second language acquisition research in recent years nevertheless, there is few research about the effectiveness of corrective feedback on speaking in Nicaragua`s elementary school settings. Therefore, this study provides relevant information about feedback and the different types of oral correction based on the categorization made by Lyster & Ranta (1997), same information that was contextualized in order that Nicaraguan teachers know how to give efficient feedback in the classroom. This project took as sample to students of fourth grade and the English teacher of the school Nelly Beatriz Castillo in the community La Rica. In the same way, it presents a guideline based on a didactic unit to develop in a month. This guideline will help teachers to apply oral corrective feedback in the oral production of the students. Also, it proposes recreates activities and it exemplify the steps to develop effective feedback during activities in the classroom.
Seminario-(Licenciados en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua
Keywords: Comunicación oral | Aprendizaje basado en tareas | Directrices-Evaluación | Inglés-Seminario-2021